Author unknown the power of anonymity in ancient Rome - Geue, Tom (Harvard University Press, 2019)
"An exploration of the darker corners of ancient Rome to spotlight the strange sorcery of anonymous literature. From Banksy to Elena Ferrante to the unattributed parchments of ancient Rome, art without clear authorship fascinates and even offends us. Classical scholarship tends to treat this anonymity as a problem or game--a defect to be repaired or mystery to be solved. Author Unknown is the first book to consider anonymity as a site of literary interest rather than a gap that needs filling. We can tether each work to an identity, or we can stand back and ask how the absence of a name affects the meaning and experience of literature. Tom Geue turns to antiquity to show what the suppression or loss of a name can do for literature. Anonymity supported the illusion of Augustus's sprawling puppet mastery (Res Gestae), controlled and destroyed the victims of a curse (Ovid's Ibis), and created out of whole cloth a poetic person and career (Phaedrus's Fables). To assume these texts are missing something is to dismiss a source of their power and presume that ancient authors were as hungry for fame as today's. In this original look at Latin literature, Geue asks us to work with anonymity rather than against it and to appreciate the continuing power of anonymity in our own time"--